(untitled) (Palestine Issues on Indonesian Society, 2025)
This paper examines the role of student movements in Indonesia’s ongoing support for Palestine, tracing the continuity and evolution of this activism from the Reformasi period (post-1998) to the present. The study explores how Indonesian student organizations have historically used the Palestinian cause as a focal point for political activism, beginning with their strong mobilization against the New Order regime’s alignment with U.S. foreign policy, and continuing with their engagement in contemporary global movements for Palestinian rights. The paper analyzes key student protests, campaigns, and organizations, considering how their activism on Palestine has adapted to the changing political landscape of Indonesia, especially in the context of democratic transition and increasing Islamic political mobilization. It also examines the influence of social media and new communication technologies on student activism, looking at how platforms like Twitter and Facebook have facilitated the mobilization of youth in support of Palestine. This study provides insights into the dynamics of youth political engagement in Indonesia and the enduring significance of Palestine in the country’s social justice movements.